Platform architecture enhances consumer decision certainty in food supply chains: the reference effect and trust transfer mechanism - Dong, Xuemei; Jiang, Baichen; Kassoh, Fallah Samuel; Chen, Feiyu (Frontiers in Sustainable Food Systems, 2025)
IntroductionThis research aims to explain how regulated digital platforms can foster sustainable food consumption. We develop and test a dual-process model of consumer logic, hypothesizing that in complex markets, consumers first use the platform’s architecture as a fast, intuitive heuristic to simplify their decision-making, before engaging in a more deliberate, analytical evaluation of supply chain attributes.MethodsWe tested the model across two complementary studies using survey data from 2,028 consumers. Study 1 employed a choice experiment grounded in prospect theory to assess the platform’s influence on choice. Study 2 utilized a structural equation model (SEM) grounded in trust theory to investigate the underlying psychological mechanism.ResultsStudy 1 demonstrated that the platform architecture functioned as a powerful reference point, triggering significant loss aversion and enabling reference-dependent variety seeking, thereby amplifying the value of attributes within its trusted boundaries. Study 2’s SEM results revealed a chain mediation effect: institutional trust in the platform architecture preceded and facilitated the development of individual trust in its component suppliers. This trust transfer process empowers the platform to function as a credible heuristic.DiscussionBy integrating behavioral economics and trust theory, this research provides a comprehensive model of platform-based consumer logic. Our novel contribution is showing how platform architecture can orchestrate a cognitive shift from heuristic simplification to analytical engagement, thus providing a powerful tool for bridging the motive-behavior gap in sustainable consumption.